The efficacy of intensive short-term dynamic psychotherapy (ISTDP) on self-esteem, emotion regulation, and defense mechanisms in men with social anxiety disorder - Kamal Mehboodi; Nuralla Mohammadi; Changiz Rahimi; Mehdi Reza Sarafraz (مجله علوم روانشناختی, 2022)
Background: Social Anxiety Disorder is considered as the most common disorder among the anxiety disorders that causes various psychological problems. Therefore, it is important to investigate the effective therapeutic interventions in order to reduce these problems. Aims: The present study evaluated the efficacy of intensive short-term dynamic psychotherapy (ISTDP) on self-esteem, emotion regulation, and defense mechanisms in people suffering from social anxiety disorder. Methods: A quasi-experimental desins of pre-test, post-test, and follow-up was used in this study. The statistical population included all men with social anxiety disorder in Shiraz who had refered to the centers of counseling, and psychological services in 1399. For this purpose20 of them were purposefully selected, and randomly assigned to the experimental, and control groups. Participants completed the self-esteem questionnaire of Cooper-Smith (1967), defense styles of Andrews et al. (1993), and emotion regulation questionnaire of Gratz (2004) before treatment. Then the experimental group received treatment sessions in 2 sessions of 60 minutes per week in 15 sessions. At the end of treatment sessions, and 2 months later, all the participants in 2 groups of experiment, and control completed the study questionairs again. Results: The results showed that ISTDP can increase self-esteem of people with social anxiety disorder (p<0.01). This therapy can affect defense mechanisms of people suffering from social anxiety disorder in the way that mature defense mechanisms increase, and immature defense mechanisms decrease in these people(p<0.01). The findings also showed that ISTDP decreases emotion dysregulation in people with social anxiety disorder (p<0.01). Conclusion: It can be said that psychotherapists can use ISTDP to improve common emotional problems, self-esteem, and ineffctive defenses in people with social anxiety disorder